Synthesis, formation and characterization of lead zinc niobate-lead zirconate titanate powders via a rapid vibro-milling method - A. Ngamjarurojana (2018)
In this study, an approach to synthesizing pyrochlore-free lead zinc niobate - lead zirconate titanate powders with a formula xPb(Zn1/3Nb2/3)O3-(1∈-∈x)Pb(Zr1/2Ti1/2)O3(when x∈=∈0.1-0.5) by a mixed oxide synthetic route via a rapid vibro-milling has been developed. The formation of perovskite phase in calcined PZN-PZT powders has been investigated as a function of calcination temperature by TG-DTA and XRD techniques. Powder morphology and chemical composition have been determined with SEM and EDX techniques. The potential of a vibro-milling technique as a significant time-saving method to obtain single-phase PZN-PZT powders at low calcination temperature is also discussed. The results indicate that at calcination condition of 900 °C for 2 h, with heating/cooling rates of 20 °C/min single-phase PZN-PZT powders can be obtained for every composition ratio between x∈=∈0.1-0.5. © 2007 Springer Science+Business Media, LLC.